A Heptacyclic Heptacycle: A Doubly Naphtho[b]thiophene Fused Borepin - Messersmith, Reid E.; Siegler, Maxime A.; Tovar, John D. (Synlett, 2018)
The synthesis and characterization of a doubly naphtho[b]thiophene fused borepin is reported herein, and the properties are compared to smaller benzo[b]thiophene and thiophene fused borepins. The synthesis involved the preparation of a symmetrical disubstituted alkyne that was reduced to a Z-olefin. This was followed by borepin formation from the alkene directly by way of thieno dilithiation. The electronic properties are consistent with extended benzannulation of the smaller analogues, and the enhancement of the brickwork type stacking is apparent as planar aromatic wings are extended from the central borepin core.
Keywords: π-conjugation; borepins; aromaticity; organic electronics; boron